‘Let's build houses': the order of housing development shaping childhood topography in Mafuyana, Maphisa - Ncube, Min'enhle (Spanish Language and Literature, 2023)
This thesis describes the physical, social and economic ordering of Mafuyana (Garikai), an urban township in Maphisa, a rural growth point in Matobo District in Matabeleland South province, Zimbabwe. It explores the ways in which this ordering informs the social construction of childhood. The township was constructed as part of Operation Garikai/Hlalani Kuhle, a housing program that served to rehouse victims of Operation Murambatsvina both of which occurred through Zimbabwe's tradition of restoring order from informal settlements for modernist planning strategies. The configuration of Operation Garikai/Hlalani Kuhle compares to the colonial framework of low-cost African housing that has historically been neglected by its municipal authorities. This neglect leads to infrastructure that is hazardous to infants. The evolutions of rural dwellings in southern Africa since the 19th Century and labour migration under colonialism – which characterised the scattering of peoples and the formation of new communities – were determined according to available resources, the physical nature of regions, the models of kinship and daily activities of rural life. Children in these contexts formed the basis of family construction, and also in Maphisa where parents or caregivers value them as a social investment during their ageing years. However, the introduction of urban infrastructure in rural Maphisa produces a framework that residents find challenging when performing their traditions of rural life in the process of raising children. The debilitating infrastructure in Mafuyana resulting from poor planning has caused residing families to face physical hardship in their dwelling. In order to habituate children into a harsh world, infant rituals associated to rural life ways in Matabeleland are performed by residents – some of which challenge modernist health discourses of cleanliness and orderliness. When makeshift endeavours on fragmented housing fail to meet their satisfaction, some residents resort to migrating – either within the township or beyond its boundaries in search for better dwelling. This scenario reflects that settling in such an ordered space lacks permanence, because locals struggle to ‘fit' into its makes, despite their efforts. The dissertation argues that the modernist developmental ordering of the growth point's township influences the developmental ordering concerned with the children that reside in it. Furthermore, examining this developmental ordering of children gives an indication on whether the housing in which they live enhances life for the growing human being.